2021
DOI: 10.5038/2577-509x.5.1.1096
|View full text |Cite
|
Sign up to set email alerts
|

The attributes of mathematics learning which Ghanaian senior high school students value

Abstract: Valuing constitutes an important aspect of mathematics pedagogy and hence student learning outcomes. This study surveyed 416 students from Cape Coast, Ghana to explore what senior high school students in this country in West Africa valued in their study of mathematics. The data collected were analyzed using principal component analysis. The results suggest that Ghanaian senior high school students found connections, understanding, fluency, learning technologies, feedback, instructional materials, open-endednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…These qualities are exploration , connection , understanding , and fluency , from highest to least in terms of the proportion of variation explained. These attributes that student teachers value regarding mathematics learning were consistent with some of the attributes Davis et al's (2021) study found among senior high school students in Ghana. Davis et al (2021) found among other things that Ghanaian senior high school students deemed connections , understanding , and fluency vital in their mathematics learning.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…These qualities are exploration , connection , understanding , and fluency , from highest to least in terms of the proportion of variation explained. These attributes that student teachers value regarding mathematics learning were consistent with some of the attributes Davis et al's (2021) study found among senior high school students in Ghana. Davis et al (2021) found among other things that Ghanaian senior high school students deemed connections , understanding , and fluency vital in their mathematics learning.…”
Section: Discussionsupporting
confidence: 83%
“…Student teachers at this tertiary institution value exploration, connections, understanding, and fluency in their study of college mathematics. These qualities largely align with some of the valuing reported by senior high school students in Ghana (see Davis et al, 2021). Our investigation of whether a statistically significant difference exists in what student teachers value across grade levels using one-way MANOVA revealed a statistically significant difference in what student teachers value in college mathematics learning across class levels.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations